Strategi Kolaborasi sebagai Pendorong Inovasi dan Kinerja UMKM di Indonesia - Novirin, Barli (Economics, Business and Management Science Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a very important role in the Indonesian economy and also function as a driving force for innovation and entrepreneurship. With flexible and adaptive characteristics, MSMEs are able to innovate and adapt to rapid market changes. The main challenges faced by MSMEs in terms of innovation and performance include limited access to resources, both financial and non-financial. In addition, the lack of knowledge and skills in information technology and digitalization is also an obstacle. In this digital era, MSMEs that are unable to utilize information technology will be left far behind by competitors. Strategic collaboration can be an effective solution to overcome the challenges faced by MSMEs in terms of innovation. This study aims to assess the impact of collaboration on innovation and performance of MSMEs in Indonesia where it can be used as a success or failure of MSME strategic collaboration in Indonesia. A qualitative approach and literature review were chosen in depth regarding the phenomenon of strategic collaboration that occurs among MSMEs in Indonesia. Therefore, it is important for MSMEs to develop a clear and measurable collaboration strategy, and to conduct periodic evaluations to ensure that the expected collaboration provides the expected benefits. Thus, strategic collaboration can be a major driver of innovation and performance of MSMEs in Indonesia, which will ultimately contribute to economic growth.